Local lymphocytes and nitric oxide synthase in the uterine cervical stroma of patients with grade III cervical intraepithelial neoplasia - Cléber Sergio da Silva; Marcia Antoniazi Michelin; Renata Margarida Etchebehere; Sheila Jorge Adad; Eddie Fernando Candido Murta (Clinics, 2010)
OBJECTIVES: Precancerous and cancerous cells can trigger an immune response that may limit tumor development and can be used as a prognostic marker. The aims of the present study were to quantify the presence of B and T lymphocytes, macrophages and cells expressing inducible nitric oxide synthase (iNOS) in the cervical stroma of women with grade III cervical intraepithelial neoplasia (CIN III) or in the intratumoral and peritumoral tissue of women with stage I invasive carcinoma. METHODS: Cervical tissue specimens were obtained from 60 women (20 each from control tissues, CIN III and invasive carcinomas). The average ages in the control, CIN III and invasive groups were 43.9 (± 4.3), 35.5 (± 9.5), and 50 (± 11.2) years, respectively. The specimens were immunohistochemically labeled with antibodies to identify T lymphocytes (CD3), cytotoxic lymphocytes (CD8), B lymphocytes (CD20), macrophages (CD68) and iNOS. We evaluated the markers in the stroma above the squamocolumnar junction (control), at the intraepithelial lesion (CIN cases), and in the nfiltrating tumor. Two independent observers performed the immunohistochemical analysis. RESULTS: T lymphocytes, B lymphocytes, macrophages and iNOS were present more frequently (P<0.05) in the stroma of peritumoral invasive tumors compared to the controls and intratumoral invasive cancer samples. CD3+ and CD20+ lymphocytes were present more frequently in CIN III patients compared to samples from patients with intratumoral invasive cancer (P<0.05). CONCLUSION: High numbers of T and B lymphocytes, macrophages and iNOS-expressing cells in the peritumoral stroma of the invasive tumors were observed. Cell migration appeared to be proportional to the progression of the lesion.